2018
DOI: 10.1093/mnras/sty1595
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and scaling relations of molecular clouds: the effect of stellar feedback

Abstract: Using hydrodynamical simulations of entire galactic discs similar to the Milky Way, reaching 4.6 pc resolution, we study the origins of observed physical properties of giant molecular clouds (GMCs). We find that efficient stellar feedback is a necessary ingredient in order to develop a realistic interstellar medium (ISM), leading to molecular cloud masses, sizes, velocity dispersions and virial parameters in excellent agreement with Milky Way observations. GMC scaling relations observed in the Milky Way, such … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 86 publications
(129 reference statements)
6
42
0
Order By: Relevance
“…We note that we do not enforce any additional refinement criterion to achieve this; the (Lagrangian) mass based refinement scheme, discussed in Section 2.5, is enough for this to be satisfied. This feedback budget has been shown to lead to Milky Way disc galaxies in close agreement to observations (Agertz & Kravtsov 2016, Agertz et al in prep), bursty star formation and realistic properties of dwarf galaxies (Read et al 2016a,b), and an interstellar medium (ISM) and structure of giant molecular clouds in excellent agreement with observations (Grisdale et al 2017(Grisdale et al , 2018.…”
Section: Galaxy Formation Physicssupporting
confidence: 83%
See 1 more Smart Citation
“…We note that we do not enforce any additional refinement criterion to achieve this; the (Lagrangian) mass based refinement scheme, discussed in Section 2.5, is enough for this to be satisfied. This feedback budget has been shown to lead to Milky Way disc galaxies in close agreement to observations (Agertz & Kravtsov 2016, Agertz et al in prep), bursty star formation and realistic properties of dwarf galaxies (Read et al 2016a,b), and an interstellar medium (ISM) and structure of giant molecular clouds in excellent agreement with observations (Grisdale et al 2017(Grisdale et al , 2018.…”
Section: Galaxy Formation Physicssupporting
confidence: 83%
“…Observationally, ff averages 1% on galactic kpc scales (Bigiel et al 2008) as well as in Milky Way giant molecular clouds (GMCs) (Krumholz & Tan 2007), albeit with a spread of several dex (Murray 2011;Lee et al 2016). Recently Grisdale et al (2019) demonstrated how high efficiencies ( ff ∼ 10%) on scales of parsecs, coupled to a feedback budget like the one adopted here, provides a close match to the observed (i.e. emerging) efficiencies on scales of individual GMCs.…”
Section: Galaxy Formation Physicssupporting
confidence: 65%
“…This effort has made it possible to model galactic outflows in a cosmological context as an emergent property of clustered star formation, with simulations now matching a range of observed galaxy properties (e.g. Hopkins et al 2014;Agertz & Kravtsov 2015, as well as properties of the turbulent ISM and giant molecular clouds (GMCs) (Grisdale et al 2017(Grisdale et al , 2018(Grisdale et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Connecting observations of GMCs to a theoretical framework for their understanding is also both pressing and difficult. Several studies have attempted to simulate GMCs in galaxies and compare their properties with observations through synthetic observations (e.g., Pan et al 2015;Ward et al 2016;Duarte-Cabral & Dobbs 2016;Richings & Schaye 2016;Grisdale et al 2018;Lakhlani et al 2019). Recently, advances in numerical methods led to cosmological scale simulations that can resolve GMC scale objects (∼ 10 5 M ), allowing a more faithful comparison, and potentially allowing us to follow their evolution through cosmic time and account for the effects of events such as galaxy mergers.…”
Section: Introductionmentioning
confidence: 99%